1990
DOI: 10.1091/mbc.1.13.1027
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dense and alpha-granule secretion from electropermeabilized human platelets: Ca(2+)-independent actions of phorbol ester and GTP gamma S.

Abstract: Electropermeabilized human platelets containing 5-hydroxy[14C]tryptamine ([14C]5-HT) were suspended in a glutamate medium containing ATP and incubated for 10 min with (in various combinations) Ca2+ buffers, phorbol 12-myristate 13-acetate (PMA), guanine nucleotides, and thrombin. Release of [14C]5-HT and beta-thromboglobulin (beta TG) were used to measure secretion from dense and alpha-granules, respectively. Ca2+ alone induced secretion from both granule types; half-maximal effects were seen at a -log [Ca2+ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
2

Year Published

1991
1991
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 49 publications
6
42
2
Order By: Relevance
“…The final concentration of SLO was 0.4 unit\ml and that of ATP was 4 mM. Additional EGTA was included to obtain a pCa value 9 (final concentration 12.5 mM) [5]. The compositions of Ca# + buffers and pCa values were calculated using the binding constants given in [22].…”
Section: Permeabilization Of Platelets With Streptolysin O and Assaysmentioning
confidence: 99%
See 4 more Smart Citations
“…The final concentration of SLO was 0.4 unit\ml and that of ATP was 4 mM. Additional EGTA was included to obtain a pCa value 9 (final concentration 12.5 mM) [5]. The compositions of Ca# + buffers and pCa values were calculated using the binding constants given in [22].…”
Section: Permeabilization Of Platelets With Streptolysin O and Assaysmentioning
confidence: 99%
“…These studies have shown that the sensitivity of secretion to Ca# + is greatly enhanced by activation of PKC [4,5]. In addition, use of this experimental system has led to the recognition of at least two distinct roles for GTP-binding proteins in secretion from platelets [5], as found in experiments with other permeabilized cells [6]. Thus GTP or its more stable analogue, guanosine 5h-[γ-thio]-triphosphate (GTP [S]) is required for the G-protein-and Ca# + -dependent activation of phospholipase C in permeabilized platelets [7], which results in the stimulation of PKC by 1,2-diacylglycerol [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations